Design of teaching materials for word problem application of quadratic function based on Newman procedure - Muhammad Rizky Syaputra; S. Suhendra; Al Jupri (Research and Development in Education (RaDEn), 2025)
An effective learning design depends on the availability of instructional materials that facilitate the teaching process for educators, enabling the achievement of learning objectives and supporting students in understanding the subject matter. This study is a qualitative study in the form of design research. This research aims to develop teaching materials for quadratic function application word problems based on the Newman procedure, to enhance students’ understanding, minimize common problem-solving errors, and improve their mathematical literacy skills. The research subjects are  grade seven students who participated in the trial of teaching materials. The design of teaching materials in this research uses the stages of the Newman procedure in solving word problems of quadratic function applications. Based on the findings during the research, after implementing the teaching materials, the authors compiled a revised teaching material design to improve the quality of the teaching material design so that it can help students reduce errors in solving quadratic function application problems and optimize students’ mathematical literacy. This teaching material design can certainly always be developed and adapted to the needs and characteristics of students.